Analysis the using of paint on external wall (case study: buildings in campus UiTM, Shah Alam) / Mukram Idris - Idris, Mukram (2002)
Outside the buildings, the life of paint film is usually thought to have ended when it is faded, dirty, chipped or scratched. This predicament almost found at numerous buildings in Malaysia and as a study case, several buildings in campus UiTM. This problem can cause divan look where the facade of that building is worst and most terrible. This situation ought to come across and try to dodge by many ways either supervise the quality of work or follow the sequence of work in painting. The type of paint chosen may be not suitable for apply to that surface and the usage of equipment may be not practical or standardised. This dissertation would focus on painting and repainting work, whish will refer to study case that focus the following: □ Identifying source of paint defect. □ Identifying problems in painting process in the selection of material, workmanship and supervision. □ Identifying solution in assuming quality painting by preceding and guideline proposal. □ Determining the best paintwork, technique and technology. In actual phenomena, all factors related to improve painting work will come out in particular by refer to study case, inspection and observation for each selected building in UiTM campus will be done base on object of study. Here, every single feature and problem is defined by overall inspection to the building The result of analysis will come out with conclusion and recommendation. Substrate must be suitably sound for painting and properly prepared. The appropriate paint system must be specified, it must be applied following manufacturer’s recommendations and under suitable conditions. UiTM Maintenance Department must administer all the contractors’ work to make certain improvement in paint quality and to ensure that the facade of building can be more energetic for a longer time without deficiency.